2015
DOI: 10.1007/s00216-015-8831-y
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemiluminescence DNA sensor array for multiplex detection of biowarfare agents

Abstract: Development of a fully automated electrochemiluminescence (ECL) DNA assay for multiplex detection of six biowarfare agents is described. Aminated-DNA capture probes were covalently immobilised on activated-carbon electrodes and subsequently hybridised to target strands. Detection was achieved via a sandwich-type assay after Ru(bpy)3(2+)-labelled reporter probes were hybridised to the formed probe-target complexes. The assay was performed in an automated microsystem in a custom designed ECL detection box with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…For this reason, the development of multiplex ECL assays for biowarfare agent is of great interest. O´Sullivan et al [ 173 ] reported the develop of a multiplex detection ECL DNA sensor for the simultaneous detection of six pathogens: Brucella, melitensis, Bacillus anthracis, Burkholderia mallei, Francisella tularensis, Bacillus thuringiensis var. kurstaki and Coxiella burnetiid .…”
Section: Ecl Dna Biosensorsmentioning
confidence: 99%
“…For this reason, the development of multiplex ECL assays for biowarfare agent is of great interest. O´Sullivan et al [ 173 ] reported the develop of a multiplex detection ECL DNA sensor for the simultaneous detection of six pathogens: Brucella, melitensis, Bacillus anthracis, Burkholderia mallei, Francisella tularensis, Bacillus thuringiensis var. kurstaki and Coxiella burnetiid .…”
Section: Ecl Dna Biosensorsmentioning
confidence: 99%
“…DNA array-based sensors: The DNA array class of detectors relies on comparing the DNA taken from microorganisms in a sample with the known DNA of known biowarfare agents. Researchers have in recent years been sequencing the DNA of an array of potential agents, using common gene sequencing methods (ESpehar-Délèze et al, 2015).…”
Section: Sensor Technologiesmentioning
confidence: 99%
“…Aptamers as molecular recognition substances appear to be excellent alternatives to antibodies due to their ease of production in vitro, wide target range, modification ease, reversible thermal denaturation, and unlimited shelf life. Recently, a number of ECL aptamer-based biosensors for the determination of a small molecule drug have been designed employing aptamers as molecular recognition elements and Ru(II) complex served as an ECL label [68] , [69] , [70] , [71] , [72] , [73] , as listed in Table 3 .…”
Section: Ecl Aptamer-based Biosensorsmentioning
confidence: 99%
“… Drugs/analytes Systems Linear ranges LOD (S/N = 3) Samples Ref. Cocaine Signal-on, Ru1-tagged aptamer/4-ABSA/ PIGE in 0.10 M PBS-0.10 M TPA (pH 7.40) 50 pM to 5 nM 10 pM [68] Cocaine Capture apt-probe assembled on Au electrode, signal apt-probe labeled with RuSiNPs in PBS (pH7.4)-1.0 M dibutylamino-ethanol 0.01–1.0 nM 3.7 pM Banknotes [69] Adenosine Sandwich type, Au electrode, Ru(phen) 3 2+ as interactor 0.5–7 nM 0.15 nM [70] Adenosine Signal off, Ru1-tagged aptamers/SWCNTs/GCE 0.1–500 nM 0.05 nM [71] Malachite green (MG) Chloramphenicol (CAP) Aptasensor array using CdS QDs and luminol-AuNPs as labels, 0.1 M PBS (pH 8.0)-12 mM H 2 O 2 0.1–100 nM MG 0.03 nM MG Fish samples [72] 0.2–150 nM CAP 0.07 nM CAP Biowarfare agents SPC electrode array (ss-DNA), Ru(bpy) 3 2+ -labeled DNA reporter, sandwich-type hybridisation assay in 300 mM PB-100 mM TPA-0.02% Triton X-100 (pH 7.6) 0–16 nM 0.6–1.2 nM for six targets [73] …”
Section: Ecl Aptamer-based Biosensorsmentioning
confidence: 99%